EFEKTIVITAS MODEL ROLE PLAYING PADA PEMBELAJARAN BERBICARA BAHASA JAWA SISWA KELAS V SEKOLAH DASAR - Novita Widyanengrum; Much Arsyad Fardani; Mohammad Syaffruddin Kuryanto (Universitas Muria Kudus, 2025)
This research was motivated by the low level of Javanese speaking skills among students. The purpose of this study was to determine the effectiveness of the role-playing model in improving Javanese speaking skills. The method used was quantitative with a one-group pretest-posttest design. The research subjects consisted of 20 fifth-grade students. Data collection techniques involved speaking tests administered before and after the treatment. The data were analyzed using normality tests and the N-Gain test to determine learning improvement. The results showed an increase in students’ speaking skills, with an average pretest score of 16.5 and a posttest score of 20.5. The N-Gain score was 0.460, categorized as moderate, with a 46% improvement percentage, indicating that learning through the role-playing model is quite effective in enhancing students’ speaking skills.